5n+7=-3

Simple and best practice solution for 5n+7=-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5n+7=-3 equation:


Simplifying
5n + 7 = -3

Reorder the terms:
7 + 5n = -3

Solving
7 + 5n = -3

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-7' to each side of the equation.
7 + -7 + 5n = -3 + -7

Combine like terms: 7 + -7 = 0
0 + 5n = -3 + -7
5n = -3 + -7

Combine like terms: -3 + -7 = -10
5n = -10

Divide each side by '5'.
n = -2

Simplifying
n = -2

See similar equations:

| 6+8x=-18 | | 3x+10=10-7x | | 0.75x+5=6 | | 6r-2r+2=7r-r | | -178-10x=44-31x | | 3-1/3= | | (5x-6)1/2=7 | | -3z-2(3+5z)= | | -8=y-6y-6 | | 1+7x=-13 | | s-9=r | | 1/2(4+6)=0 | | x^1/2+x=0 | | 78-7x=20x+15 | | -9=r | | -(7x-4)+4x-5=-1 | | 6-10x=39-17x | | -144=-12x | | -(6x-4)+4x-6=-2 | | 11.4(x+3)+2=4.5(x+1) | | 5n-2n=-9 | | -12*12= | | 2.625=fraction | | 5=5+2m+3m | | 12*-12= | | 7(-16)(0)(-3)= | | Y=-25+4(x+5) | | x+x+4+3(x)+7=71 | | 1x+8=8x+22 | | 9x=3y-6 | | 13x+5=1x+11 | | 0.5a+2=5 |

Equations solver categories